2013
DOI: 10.1017/s1431927613013445
|View full text |Cite
|
Sign up to set email alerts
|

Histochemistry and Ultrastructure of Urocytes in the Pupae of the Stingless BeeMelipona quadrifasciata(Hymenoptera: Meliponini)

Abstract: The main cell types of the adult bee fat body are trophocytes and oenocytes; however, in pupae of some newly emerged bees, trophocytes are modified into cells called urocytes, which possibly function as a substitute for Malpighian tubules during metamorphosis when larval tubules are not functional and/or storage of urate salts is required. This study evaluated the morphology of urocytes in the stingless bee Melipona quadrifasciata and the possibility of maintaining these cells in primary culture. The urocytes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…İzzetoğlu & Gülmez, 2019), the fat body is composed of only trophocytes and oenocytes. In Melipona quadrifasciata, in addition to trophocytes and oenocytes, urocytes are also present (Furtado et al, 2013). The study of Park et al (2013) showed that P. americana possesses trophocytes, urocytes and mycetocytes but no oenocytes in its fat body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…İzzetoğlu & Gülmez, 2019), the fat body is composed of only trophocytes and oenocytes. In Melipona quadrifasciata, in addition to trophocytes and oenocytes, urocytes are also present (Furtado et al, 2013). The study of Park et al (2013) showed that P. americana possesses trophocytes, urocytes and mycetocytes but no oenocytes in its fat body.…”
Section: Discussionmentioning
confidence: 99%
“…Hymenoptera) and Lepidoptera, and they take on the role of Malpighi tubules (Arrese & Soulages, 2010;Chapman, 2013;Furtado et al, 2013;Landim & Oliveira, 2006). In P. americana (Dean et al, 1985;Locke, 1984;Park et al, 2013;Wigglesworth, 1987) and B.…”
Section: Discussionmentioning
confidence: 99%
“…In insects, urate is typically deposited in specialized cells – so-called urocytes [32] – which together with trophocytes [32] and oenocytes [33] represent the three major cell types in the fat body. Urocytes store urates either in vacuoles or as circular, birefringent spherocrystals [32], and can occupy a large fraction of the fat body, for instance in the termite Mastotermes darwiniensis [32].…”
Section: Discussionmentioning
confidence: 99%
“…In the termite Reticulitermes flavipes , uric acid is recycled by gut bacteria as a nitrogen source [34], and urate deposits have been linked to oocyte development [35]. In Pachycondyla ants, urocytes specialize in the storage of nutrients and excretion products [36] and a composition assay in Melipona quadrifasciata bees identified Na, Ca, Mg, P as main elements in urocytes, as well as traces of Zn, Mn, and K [33]. In C. obscurior we found circular, birefringent spherocrystals but no cell nuclei, indicating that urate is deposited directly.…”
Section: Discussionmentioning
confidence: 99%
“…It is important to point out that sterile samples extractions must be performed in a laminar flow chamber, with the material previously sterilized by ultraviolet light for 25 minutes. Besides, it is recommended that the larvae are disinfected by immersion in 70% alcohol for 1 minute, washing by immersion in autoclaved water for 1 minute (2x) and let them dry on autoclaved filter paper for approximately 2 minutes [52,53], or by raising larvae in vitro in a sterile environment.…”
Section: Materials Used In the Extractionmentioning
confidence: 99%